Study on the mechanical and thermal properties of polylactic acid/hydroxyapatite@polydopamine composite nanofibers for tissue engineering. Issue 36 (11th February 2020) - Hu, Shengyu; Wu, Jiahui; Cui, Zhixiang; Si, Junhui; Wang, Qianting; Peng, Xiangfang
Abstract: Electrospun nanofibers have attracted tremendous attention because of their similar structure with extracellular matrix. In this work, the polydopamine (PDA) coating layer was first applied to modify hydroxyapatite (HA) nanoparticles and obtain functional HA@PDA nanoparticles. Subsequently, the polylactic acid (PLA)/HA@PDA composite nanofibers were prepared via electrospinning. The hydrophilicity and water absorption of PLA/HA@PDA composite nanofibers were larger than those of PLA and PLA/HA composite nanofibers. The thermal stability, static and dynamic mechanical properties of PLA/HA@PDA composite nanofibers significantly increased because the PDA coating layer on the surface of the HA nanoparticles acted like a glue‐like transition layer, which led to an increase in interfacial adhesion between HA@PDA nanoparticles and the PLA matrix. The attachment and viability of mouse embryonic osteoblast cells (MC3T3‐E1) cultured on the PLA/HA@PDA composite nanofibers were significantly increased compared with those cultured on the PLA and PLA/HA composite nanofibers. These results suggested that the PLA/HA@PDA composite nanofibers have superior mechanical and biological properties, which makes it potentially useful for tissue engineering scaffolds. Abstract :